Hydroxyl Radical-Based Processes for Decolourization of Direct Blue 71: A Comparative Study - Maleki, Afshin; Hossein Mahvi, Amir; Shahmoradi, Behzad (Asian Journal of Chemistry, 2011)
Advanced oxidation processes are based on the generation of powerful oxidants such as hydroxyl radicals that are non-selective and much more powerful than other oxidants. Hydroxyl radicals are widely used to degrade organic products in industrial waste water, especially dye containing effluents. The objectives of this study were to investigate the hydroxyl radical-based processes for decolourization of direct blue 71. Decolourization of aqueous direct blue 71 using ultraviolet radiation and ultrasonic irradiation with and without hydrogen peroxide was investigated in a laboratory-scale batch photoreactor and sonoreactor with emphasis on the effect of various parameters on decolouration and degradation efficiency. The toxicity was also evaluated in acute toxicity studies using Daphnia magna. Results showed that, colour removal efficiencies by ultrasonic irradiation (US) and ultrasonic irradiation plus hydrogen peroxide (US/H2O2) processes were negligible. Almost complete disappearance of direct blue 71 after 5 min of irradiation in UV/H2O2 process was possible to achieve. The results clearly showed that dye examined was toxic to Daphnia magna and resulted in quite low LC50 value. The decolourization efficiency was found to increase with increasing H2O2 concentration, however, the marginal benefit became decreasing with further increasing of H2O2 due to the scavenging effect of excess H2O2. The rate of colour decay followed pseudo-first order kinetics with respect to the UV-visible absorption of the test dye during reaction.